Staged and non-staged anaerobic filters : microbial activity segregation, hydrodynamic behaviour and performance - Alves, M. M. (1998)
This work describes a comparative study of staged and non-staged anaerobic flters for treating a synthetic dairy waste under similar operating conditions. The effect of increasing the substrate concentration from 3 to 12 g COD dmˉ³ at a constant hydraulic residence time (HRT) of 2 days was evaluated with respect to overall reactor performance, biogas production, volatile fatty acids profiles along the height, methanogenic and acidogenic activity distribution, and hydrodynamic behaviour. The potential maximum specific methanogenic activity against acetate, hydrogen, propionate and butyrate and the lactose specific activity were determined for sludge sampled from three different points in each reactor, under two operating conditions (influent COD of 3 and 9 g COD dmˉ³). Although all trophic groups involved in the anaerobic process were found throughout the reactors, it was possible to identify different specific sludges at different heights in both reactors. Performances of the two configurations were very similar under the operating conditions tested and the plug flow behaviour of the staged reactor was clearly reduced when the influent concentration increased from 3 to 9 g COD dmˉ³.